The consequences of foreign reserves, FDI, inflation, exports, and imports on Pakistani exchange rate - Mazher, Muhammad Ahmad; Tramankuti, Yasotha Nair; Osman, Zurul Aisya (Journal of Commerce, Management, and Tourism Studies, 2023)
This study uses monthly data sources from the State Bank of Pakistan to examine the impact of inflation, exports, foreign direct investment, foreign reserves, and imports on Pakistan's currency exchange rates from July 2018 to January 2023. The empirical results demonstrate that inflation and imports have a positive and significant effect on the exchange rate in the short term by using the ARDL bound test. Exchange rates are negatively impacted by exports, foreign direct investment, and foreign reserves. Inflation, imports, and foreign reserves have a positive and considerable influence on currency exchange rates over the long term.